Stress corrosion cracking of E690 steel as a welded joint in a simulated marine atmosphere containing sulphur dioxide. (November 2015) - Ma, H.C.; Liu, Z.Y.; Du, C.W.; Wang, H.R.; Li, X.G.; Zhang, D.W.; Cui, Z.Y.
Highlights: The various microstructures of the welded joint were characterized and their electrochemical properties were measured by conventional and localized electrochemical methods. An original device was set up to investigate the SCC behavior in simulated marine atmosphere containing SO2 . The most vulnerable location of the welded joint was found out and the effect of M-A constituents on SCC was illustrated. Abstract: Stress corrosion cracking (SCC) behavior and mechanism of E690 welded joint in simulated marine atmosphere containing SO2 were investigated using SSRT method and electrochemical measurements. Results showed that it had very high SCC susceptibility in this environment with a combined mechanism of anodic dissolution and hydrogen embrittlement (HE). The intercritical heat affected zone in the welded joint was the most vulnerable location to SCC because this zone has less strength, more negative potential, and higher corrosion current density. The M-A constituents had a detrimental effect on SCC behavior in the synergetic effect of stress concentration, micro-galvanic corrosion, and HE.